Exploring the potential development of digital modules for arts and culture learning based on local culture: A mixed-method study on Bedhaya Ketawang dance - Astuti, Widhi; Nurkamto, Joko; Subiyantoro, Slamet; Rochsantiningsih, Dewi (Edelweiss Applied Science and Technology, 2024)
The need for digital module development in arts and cultural education has become increasingly urgent, especially considering the lack of educational media relevant to local cultural contexts. In today’s digital era, integrating traditional cultural values with educational technology is essential for preserving cultural heritage and enhancing education quality. Bedhaya Ketawang dance, rich in philosophical and historical values, offers significant potential as an interactive digital learning module. This study aims to identify the needs of students and teachers in developing a digital teaching module based on Bedhaya Ketawang. The study employed a mixed-method approach, gathering quantitative data through a survey distributed to 87 students, alongside qualitative data collected through interviews and observations with two arts and culture teachers. Research instruments included questionnaires, interview guidelines, and learning observation tools. The data were descriptively analyzed using simple statistical and interactive qualitative analyses. The findings show that while students understand the local culture, their practical engagement remains limited. A total of 80% of students reported that more interactive digital media would enhance their learning process, and 83% expressed a desire for increased use of digital media in arts and cultural education. Interviews and observations revealed that current digital media are passive and suboptimal for promoting student engagement. In conclusion, developing a digital module based on Bedhaya Ketawang is crucial for improving student engagement and understanding the local culture. The implications of this research suggest the need for more innovative, contextual, and relevant curricula to meet the demands of 21st-century education.